Peningkatan Kepatuhan Pembayaran Iuran JKN Pada Peserta Mandiri Melalui Edukasi Keuangan dan Kesehatan - Fadillah Ulva; Nursya, Febriyanti (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
The higher number of independent BPJS Health participants is not in line with the level of compliance of these independent participants in paying JKN contributions. Compliance in paying JKN contributions is the obedience and willingness of a health insurance participant. Many factors cause individual national health insurance participants to be non-compliant in paying contributions every month. One of them is income and history of catastrophic illness. Compliance in paying JKN contributions is one of the things that affects the stability and sustainability of the JKN program. The purpose of the community service activities carried out is to improve the compliance of independent JKN participants in making contribution payments. Community service activities are carried out in the Puskesmas X Working Area in Padang City. Community service activities are carried out through financial and health education with lecture and discussion methods. The target of this activity is JKN contribution participants in the working area of Puskesmas X. After community service activities, there was an increase in knowledge and awareness in the community regarding compliance with JKN contribution payments.